Branched PCL-Based Thermogelling Copolymers: Controlling Polymer Architecture to Tune Drug Release Profiles - Lin, Qianyu; Ow, Valerie; Boo, Yi Jian; Teo, Vincent T. A.; Wong, Joey H. M.; Tan, Rebekah P. T.; Xue, Kun; Lim, Jason Y. C.; Loh, Xian Jun (Frontiers in Bioengineering and Biotechnology, 2022)
Temperature-responsive hydrogels, or thermogels, are a unique class of biomaterials that show facile and spontaneous transition from solution to gel when warmed. Their high biocompatibility, and ease of formulation with both small molecule drugs and biologics have made these materials prime candidates as injectable gel depots for sustained local drug delivery. At present, controlling the kinetics and profile of drug release from thermogels is achieved mainly by varying the ratio of hydrophobic: hydrophilic composition and the polymer molecular weights. Herein, we introduce polymer branching as a hitherto-overlooked polymer design parameter that exhibits profound influences on the rate and profile of drug release. Through a family of amphiphilic thermogelling polymers with systematic variations in degree of branching, we demonstrate that more highly-branched polymers are able to pack less efficiently with each other during thermogel formation, with implications on their physical properties and stability towards gel erosion. This in turn resulted in faster rates of release for both encapsulated small molecule hydrophobic drug and protein. Our results demonstrate the possibility of exploiting polymer branching as a hitherto-overlooked design parameter for tailoring the kinetics and profile of drug release in injectable thermogel depots.